The decisive study: defining beta-lactam concentration in Intensive care unit patients. - Mat Nor, Mohd Basri; Mazlan, Mohd Zulfakar; Sulaiman, Helmi; Kamarulzaman, Adeeba; Hasan, Mohd Shahnaz; Wan Mat, Wan Rahiza (International Islamic University Malaysia, 2020)
Summary of Research Findings: 1. Patients age, estimated CLcr and recent surgery significantly predicted the Vd and CL of both beta-lactams. Piperacillin and meropenem concentrations were highly-variable with coefficient of variation (COV) of ≥67.7%. Forty-nine patients (58.3%) achieved the PK/PD target and they tend to be older, with slower CLcr and receiving continuous infusion. Based on the most parsimonious logistic regression model, higher CLcr and intermittent infusion were significant predictors of sub-optimal PK/PD target attainment.